Interfacial texture-driven failure behaviors of Gd/Yb co-doped YSZ thermal barrier coatings under thermal cyclic loading: Design and optimization - Kehan Yang; Junmiao Shi; Kaiming Zhang; Xiaolong Chen; Fuqiang Tian; Song Wu; Xiancheng Zhang (Journal of Materials Research and Technology)
Double ceramic layer (DCL) thermal barrier coatings (TBCs) with excellent thermal shock resistance have been developed but are weakest at the inter-ceramic interface. It is desirable to improve the interfacial bonding between the ceramic layers to further enhance service reliability. In this study, an interfacial texture deposition strategy was proposed to strengthen the inter-ceramic interface of the self-developed DCL TBCs. Specifically, eight interfacial textures were deposited at the interfaces between YSZ and RYSZ (where R represents two rare-earth oxides, Gd2O3 and Yb2O3, R = 6.5 wt%) layers, followed by thermal cycling tests to explore their critical roles in the failure behaviors of DCL TBCs. Microstructural evolutions, phase compositions, and stress variations were investigated in detail. The relationship between texture and interfacial separation was identified. A denser texture spacing led to a smaller flaking area. Ultimately, the coating performance reached its optimum when the interfacial texture had a diameter of 2.5 mm, a spacing of 1.5 mm, and a height of 200 μm. After 230 thermal cycles at 1150 °C, the flaking area was only 23 % of that observed in untextured TBCs, and the layer RYSZ did not undergo phase transformation. This study provides theoretical support for interfacial texture and lanthanide-doped YSZ design of TBCs.